2013
DOI: 10.1093/europace/eut363
|View full text |Cite
|
Sign up to set email alerts
|

Procedural sedation with dexmedetomidine during ablation of atrial fibrillation: a randomized controlled trial

Abstract: Procedural sedation with dexmedetomidine may assure safety and patient immobility during AF ablation, and therefore may be a potential alternative for that with GABAergic anaesthetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 17 publications
0
27
1
Order By: Relevance
“…14 It is also used for sedation in the intensive care unit. Recently, it was reported that dexmedetomidine is often used as an adjuvant for general anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…14 It is also used for sedation in the intensive care unit. Recently, it was reported that dexmedetomidine is often used as an adjuvant for general anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Irrespective of this compromise, the pattern of complications did not deviate largely from the safety profile of the sedatives that were commonly used for each procedure. For example, DEX induces sedation by sympatholytic effects through stimulation of α 2A -adrenoceptors in the locus ceruleus, resulting in a minimized risk for respiratory depression to a greater extent than other sedatives, including PF [21], MDZ [21, 24], and TIA [25]. By increasing parasympathetic activity, however, DEX induces bradycardia.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was significantly more hypotension at 60 and 120 minutes in the dexmedetomidine–remifentanil group. The second trial by Sairaku et al randomized 87 patients to dexmedetomidine with rescue thiamylal (a barbiturate) versus thiamylal only targeting moderate sedation using a PDNA model; both groups also received pentazocine (an opioid analgesic). The incidence of hypotension and bradycardia were similar between groups.…”
Section: Ep Procedures—evidence For Sedation Practicesmentioning
confidence: 99%
“…Although the provision of GA requires a dedicated anesthesia provider, controversy exists as to whether intravenous sedation in this complex patient population can or should be undertaken by a proceduralist‐directed nurse‐administered (PDNA) model. In a recent survey of 38 national academic centers, electrophysiologists noted that in 26.3% of EP cases, an anesthesiologist is warranted most of the time or always due to patient complexity, yet there is also ample literature espousing the safety and benefits of PDNA sedation for these cases . Moreover, intended sedation plans may require modification over the course of a procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation